Formation Process of Zircon Associated with REE‐Fluorocarbonate and Niobium Minerals in the Nechalacho REE Deposit, Thor Lake, Canada. Issue 1 (20th December 2012) - Hoshino, Mihoko; Watanabe, Yasushi; Murakami, Hiroyasu; Kon, Yoshiaki; Tsunematsu, Maiko
Abstract The two drill holes, which penetrated sub‐horizontal rare earth element (REE) ore units at the Nechalacho REE in the Proterozoic Thor Lake syenite, Canada, were studied in order to clarify the enrichment mechanism of the high‐field‐strength elements (HFSE: Zr, Nb and REE). The REE ore units occur in the albitized and potassic altered miaskitic syenite. Zircon is the most common REE mineral in the REE ore units, and is divided into five types as follows: Type‐1 zircon occurs as discrete grains in phlogopite, and has a chemical character similar to igneous zircon. Type‐2 zircon consists of a porous HREE‐rich core and LREE–Nb–F‐rich rim. Enrichment of F in the rim of type‐2 zircon suggests that F was related to the enrichment of HFSE. The core of type‐2 zircon is regarded to be magmatic and the rim to be hydrothermal in origin. Type‐3 zircon is characterized by euhedral to anhedral crystals, which occur in a complex intergrowth with REE fluorocarbonates. Type‐3 zircon has high REE, Nb and F contents. Type‐4 zircon consists of porous‐core and ‐rim, but their chemical compositions are similar to each other. This zircon is a subhedral crystal rimmed by fergusonite. Type‐5 zircon is characterized by smaller, porous and subhedral to anhedral crystals. The interstices between small zircon grains are filled by fergusonite. Type‐4 and type‐5 zircon grains have low REE, Nb and F contents. Type‐1 zircon is only included in one unit, which is less hydrothermally altered and mineralized. Type‐2 and type‐3 zircon grains mainly occur in the shallow units, while those of type‐4 and type‐5 are found in the deep units. The deep units have high HFSE contents and strongly altered mineral textures (type‐4 and type‐5) compared to the shallow units. Occurrences of these five types of zircon are different according to the depth and degree of the hydrothermal alteration by solutions rich in F and CO3, which permit a model for the evolution of the zircon crystallization in the Nechalacho REE deposit as follows: (i) type‐1 (discrete magmatic zircon) is formed in miaskitic syenite. (ii) LREE–Nb–F‐rich hydrothermal zircon formed around HREE‐rich magmatic zircon (type‐2). (iii) type‐3 zircon crystallized through the F and CO3‐rich hydrothermal alteration of type‐2 zircon which formed the complex intergrowth with REE fluorocarbonates; (iv) the CO3‐rich hydrothermal fluid corroded type‐3, forming REE–Nb‐poor zircon (type‐4). Niobium and REE were no longer stable in the zircon structure and crystallized as fergusonite around the REE–Nb‐leached zircon (type‐4); (v) type‐5 zircon is formed by the more CO3‐rich hydrothermal alteration of type‐4 zircon, suggested by the fact that type‐4 and type‐5 zircon grains are often included in ankerite. Type‐3 to type‐5 zircon grains at the Nechalacho REE deposit were continuously formed by leaching and/or dissolution of type‐2 zircon in the presence of F‐ and/or CO3‐rich hydrothermal fluid. These mineral associations indicate that three representative hydrothermal stages were present and related to HFSE enrichment in the Nechalacho REE deposit: (i) F‐rich hydrothermal stage caused the crystallization of REE–Nb‐rich zircon (type‐2 rim and type‐3), with abundant formation of phlogopite and fluorite; (ii) F‐ and CO3‐rich hydrothermal stage led to the replacement of a part of REE–Nb–F‐rich zircon by REE fluorocarbonate; and (iii) CO3‐rich hydrothermal stage resulted in crystallization of the REE–Nb–F‐poor zircon and fergusonite, with ankerite. REE and Nb in hydrothermal fluid at the Nechalacho REE deposit were finally concentrated into fergusonite by way of REE–Nb–F‐rich zircon in the hydrothermally altered units.